A novel human ex vivo skin model to study early local responses to burn injuries - Elisabeth Hofmann (Nature Portfolio, 2021)
Abstract Burn injuries initiate numerous processes such as heat shock response, inflammation and tissue regeneration. Reliable burn models are needed to elucidate the exact sequence of local events to be able to better predict when local inflammation triggers systemic inflammatory processes. In contrast to other ex vivo skin culture approaches, we used fresh abdominal skin explants to introduce contact burn injuries. Histological and ultrastructural analyses confirmed a partial-thickness burn pathology. Gene expression patterns and cytokine production profiles of key mediators of the local inflammation, heat shock response, and tissue regeneration were analyzed for 24 h after burn injury. We found significantly increased expression of factors involved in tissue regeneration and inflammation soon after burn injury. To investigate purely inflammation-mediated reactions we injected lipopolysaccharide into the dermis. In comparison to burn injury, lipopolysaccharide injection initiated an inflammatory response while expression patterns of heat shock and tissue regeneration genes were unaffected for the duration of the experiment. This novel ex vivo human skin model is suitable to study the local, early responses to skin injuries such as burns while maintaining an intact overall tissue structure and it gives valuable insights into local mechanisms at the very beginning of the wound healing process after burn injuries.